Medium and long‐term efficacy of psychoeducational family intervention for bipolar I disorder: Results from a real‐world, multicentric study. (9th February 2022) - Luciano, Mario; Sampogna, Gaia; Del Vecchio, Valeria; Giallonardo, Vincenzo; Di Cerbo, Arcangelo; Palummo, Carmela; Malangone, Claudio; Lampis, Debora; Veltro, Franco; Bardicchia, Francesco; Ciampini, Giusy; Orlandi, Emanuele; et al.
Abstract: Objectives: This study aims to explore the long‐term efficacy of a psychoeducational family intervention (PFI) in bipolar I disorder at one and five years post‐intervention in terms of improvement of: (1) patients' symptoms and global functioning and (2) relatives' objective and subjective burden and coping strategies. Methods: This is a multicentre, real‐world, controlled, outpatient trial. Recruited patients and key‐relatives were consecutively allocated to the experimental intervention or treatment as usual. Patients were assessed at baseline, and after one and five years. Results: One hundred and thirty‐seventh number families have been recruited; 70 have been allocated to the experimental intervention, and 67 have been allocated to the control group. We observed an increasing positive effect of the PFI on patients' clinical status, global functioning and objective and subjective burden after one year. We also found a reduction in the levels of relatives' objective and subjective burden and a significant improvement in the levels of perceived professional support and of coping strategies. The efficacy of PFI on patients' clinical status was maintained at five years from the end of the intervention, in terms of relapses, hospitalizations and suicide attempts. Conclusions: The study showed that the provision of PFI in real‐world settings is associated with a significant improvement of patients' and relatives' mental health and psychosocial functioning in the long term. We found that the clinical efficacy of the intervention, in terms of reduction of patients' relapses, hospitalization and suicide attempts, persists after 5 years. It is advisable that PFI is provided to patients with BD I in routine practice.